Decadal Stabilization of Soil Inorganic Nitrogen as a Benchmark for Global Land Models. (17th April 2019) - Wei, Ning; Cui, Erqian; Huang, Kun; Du, Zhenggang; Zhou, Jian; Xu, Xiaoni; Wang, Jing; Yan, Liming; Xia, Jianyang
Abstract: Global land models are now routinely incorporating the nitrogen (N) cycle into simulations, but the identification of its benchmarks has lagged behind. An important variable in these models is the soil inorganic N (SIN) which is the resultant of different input and output N processes. However, whether and how the SIN pool and its spatiotemporal variation can be used as benchmarks for models remains unclear. Here we first constructed a database of measured SIN at 756 sites from 1980 to 2010 across China, one of the regions that has been experiencing the highest external N input. Although there was great spatial variability of the measured SIN pool, no significant changes were detected across China during 1980–2010 based on a bootstrapping approach. The medians of the measured SIN across China were 63, 70, and 65 mg/kg during the 1980s, 1990s, and 2000s, respectively. Then, we used the regional SIN database to evaluate two versions of the Community Land Model (i.e., CLM4.5 and CLM5.0). In comparison with the observation (median 75 mg/kg) at grid‐cell scale, both CLM4.5 (median 0.70 mg/kg) and CLM5.0 (median 0.79 mg/kg) underestimated the SIN pools across China. Although the drivers of such modeling biases are difficult to identify at the current stage, improved representations of both input and output processes of the SIN pool in the models are highly recommended. These findings suggest that a decadal stabilization of the SIN pool in terrestrial ecosystems and the spatial distribution of the SIN pool may be a useful benchmark for global biogeochemical models. Key Points: Soil inorganic nitrogen showed large spatial heterogeneity across China No temporal trend of soil inorganic nitrogen concentration was detected across China during the past three decades Large biases exist when estimating the soil inorganic nitrogen pool in current global land models